Evaluasi Pengolahan Air Lindi di Area Penimbunan Tailing, Fly Ash, Bottom Ash Berdasarkan Parameter pH, TSS dan Fe (Studi Kasus pada Salah Satu Industri Pengolahan Bauksit di Kalimantan Barat) - Nini Malasari; Weli Zuandi; Rizky Putranto (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study aimed to evaluate the effectiveness of the leachate treatment system at a tailings, fly ash, and bottom ash disposal facility of an alumina processing company based on pH, Total Suspended Solids (TSS), and iron (Fe) parameters. A descriptive quantitative research method was employed by collecting leachate samples from the inlet and outlet for five consecutive days. The pH and TSS parameters were measured directly in the field, while Fe concentrations were analyzed in an accredited laboratory. Treatment effectiveness was assessed by comparing water quality before and after treatment in accordance with the effluent quality standards stipulated in the Indonesian Ministry of Environment Regulation No. 34 of 2009. The results showed that the leachate pH was successfully reduced from 12.6–12.7 to 7.2–8.8, meeting the applicable quality standards. TSS concentrations also decreased from 239–798 mg/L to 11–385 mg/L, with an average removal efficiency of 77.47%, and most samples complied with the regulatory standards. In contrast, Fe concentrations increased from 0.42 mg/L to 22.1–30.5 mg/L after treatment, exceeding the maximum allowable limit of 5 mg/L. This increase indicates that the treatment system was ineffective in controlling Fe concentrations, which was likely caused by the remobilization of Fe(OH)₃ precipitates or chemical reactions occurring during the neutralization process. Overall, the leachate treatment system was effective in reducing pH and TSS but requires improvement in Fe removal, particularly during the neutralization and polishing pond stages.